A Mobile and Height-adjustable Smoker for Calming Giant Honeybees (Apis dorsata) - Jayasena, K.M.N.M.; Kahandage, P.D.; Kosgollegedara, E.J.; Sirisena, U.G.A.I.; Senevirathne, N.D.S.L. (New Countryside, 2024)
The giant honeybees (Apis dorsata) plays an important role as pollinators, which are vital in plant reproduction. They help the forest and perennial crops by mediating speciation, promoting genetic diversity, and contributing to ecosystem stability. They live in large colonies with vertical comb and commonly make nests in natural sites and manmade structures. If disturb they may aggressive and attack the inhabitants in the area. Therefore, removal of their nest is a common practice especially when they are located in populated places. The removal of the nests can be harmful to the bees and destruction of colonies with fire is commonly reported. It would be more prudent to use mild smoke to disperse the bees and relocate the comb to a safer location. Unfortunately, there is currently no safe and reliable smoking device available to reach inaccessible combs. This study aims to introduce a new height-adjustable smoker as a solution for this problem. The smoker includes a combustion chamber and a pumping and delivery unit. The performance of the smoker was evaluated in Anuradhapura area using existing combs near human settlements. Different compaction levels of smoking fuel (a mixture of rice straw and guinea grass in a 1:1 ratio) were tested, and measurements were taken for firing time, smoke flow rate, total time, and smoke temperature. The data was then analyzed using ANOVA with a Complete randomized design at a significance level of p<0.05. The optimal compaction level for smoke generation was determined to be 67.5 g/ L. At this level, the firing time, smoke flow rate, and temperature were 21 minutes, 18.5 L/minute, and 37°C, respectively. It took only 8 mins to completely disperse giant honeybees from the colony. Therefore, the smoker can be recommended as an effective and safe method for dealing with giant honeybees.